COVID-19 Treatment: The Race Against Time - Aljofan, Mohamad; Gaipov, Abduzhappar (MODESTUM LTD, 2020)
The new outbreak ofthe novel coronavirus infection emerged inWuhan- China in late 2019, by the end of Mar 2020, it has spread in more than 178 countries and territories. There is no vaccine or antiviral treatment for COVID-19. Currently, there are several drugs and vaccines being tested for their potential activity against the disease. In this review, we briefly discuss some of the investigational drugs and vaccines being tested against COVID-19 as well as their potential drawbacks.
Keywords: COVID-19; treatment; clinical trials; Chloroquine; Lopinavir-ritonavir; Remdesivir; Tocilizumab; Camostat mesilate